The health influence on returns to education in Brazil: A nonlinear approach - Letícia Xander Russo; Joilson Dias (EconomiA, 2016)
This paper investigates the returns to education in terms of individuals' health in Brazil. We use the Heckman procedure (1979) and a nonlinear model that allows the consideration of the existence of increasing returns. The study employs microdata from National Survey by Household Sample for 2003 and 2008. The health status is measured by self-assessment of individuals. We determine that the rate of returns decreases until the fourth and fifth years of schooling, that is, until the completion of primary education when increasing returns start. The evidence also indicates that the rate of return to education is lower for individuals in poor health; for people with 15 or more years of schooling, the rate of return is 10–14.5% lower for those who are unhealthy. – – O artigo investiga o efeito do estado de saúde individual na taxa de retorno da educaç\~ao. O método empregado consiste em um modelo n\~ao linear, que permite a existência de retornos crescentes, e no procedimento de Heckman (1979). O estado de saúde é mensurado pela autoavaliaç\~ao dos indivíduos. Com base nos dados da PNAD de 2003 e 2008, é encontrado que a taxa de retorno da educaç\~ao decresce até o quarto e quinto ano de escolaridade, isso é, o retorno se torna crescente apenas a partir da conclus\~ao das séries iniciais do ensino fundamental. Os resultados também apontam que a taxa de retorno é inferior para indivíduos que n\~ao referiram uma boa saúde; para indivíduos com 15 ou mais anos de escolaridade, a taxa de retorno é de 10% a 14.5% menor para indivíduos n\~ao saudáveis.
Keywords: I1; I2; J2; 330; Return to education; Health; Nonlinear model